Um gozo explosivo para a antipoética pornoterrorista de Diana J. Torres - Madeiros, Jose Eider (2020)
This dissertation seeks to understand, in the dissident voice of Diana J. Torres' postpornographic language, aka Diana Pornoterrorista, the manifestation of a jouissance through antipoetics, based on the dialogical relations between literature and psychoanalysis. The literary selection focus on the analysis of “Sin título”, “Animal”, “Mi vagina” e “Transfrontera” as demonstration poems of what is based on Pornoterrorismo (2011) and what is mixed as a rupture of the characteristic style of the post- pornographic in postmodernism, a gap in the symbolic and in submission to the phallic law resulting from the not-all feminine, and uncanny recurrence to the imagery of the abject, the grotesque and the pathological as a way of resignifying the bodies inscribed under the imprecise and indeterminate aegis of queer. To this end, we present a summary history of the presence of whores as characters in Western literature that have been named, in order to approximate the mark of subjectivity in fictional representation from classical writings to the productions of the mid-19th century, associating this nomination with a certain recognition of constitution of subject in these characters. Therefore, we engage in the discussion of theory on themes related to the feminine as a pulsating body, a phantasmatic representation in the imaginary, and a destabilizing sign of the symbolic order, based on the varied writings of Freud and Lacan, and their critics and commentators. In order to illustrate the pornoterrorist antipoetics as a symptom of the contemporary, we essay approximations around pornographic intersemiosis and jouissance, through a psychoanalytical look, as fissures appropriated by pro-sex feminism and post-pornographic narratives in face of the determinisms of the empire of images, but creatively linked to the ambivalence of the feminine as indeterminable, open, terrific.